Verbal Humor in the Online Comic "Ukik_Rm" - Muhammad Haekal Harahap; Mulyadi; Alemina Br. Perangin-angin (RETORIKA: Jurnal Ilmu Bahasa, 2023)
The aim of this research are (1) describing the knowledge recources that build verbal humor in online comics ukik_rm and (2) classifying the types of verbal humor that exist in online comics ukik_rm. To achieve the objectives of this study, Semantics Script Theory of Humor (SSTH), General Theory of Verbal Humor (GTVH), and 12 types of verbal humor Shade were used. This research data is humorous text in online comics ukik_rm. The comics are taken from the official Instagram account of ukik_rm online comics (ukik_rm). This research applied qualitative-descriptive approach. The note-taking method is used in collecting data. in analyzing the data used the data analysis method of Miles and Huberman.The results of this study show that every knowledge resource that exists and builds verbal humor of online comics ukik_rm has a decisive and important role for the humor of verbal humor of online comics ukik_rm. Script opposition that is often found in the verbal humor of online comics ukik_rm is the opposition between two scripts that come from things close to Indonesian society. For logical mechanisms, "faulty reasoning" is a type of LM that is often used. Situations that are often used are situations that are based on everyday life. The target of verbal humor is imposed on a group or an individual. The narrative strategy is a strip comic. The language consistently uses set up and punch line techniques. The types of verbal humor found in objects are pun, joke, satire, farce, irony, and sarcasm.